2021
DOI: 10.1016/j.ejvsvf.2021.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Unsuccessful Stent Graft Repair of a Hepatic Artery Aneurysm Presenting with Haemobilia: Case Report and Comprehensive Literature Review

Abstract: Aims To discuss treatment strategies for non-traumatic, non-iatrogenic hepatic artery aneurysms (HAAs) in the presence of an arteriobiliary fistula, illustrated by a case and followed by a comprehensive review of the literature. Methods Following the PRISMA guidelines, 24 eligible HAA cases presenting with haemobilia were identified. Characteristics of patients, aneurysms, treatment strategies and their outcomes were collected. Results A 69 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Postoperative complications were reported in five cases (13.5%) [19,35,39,41,43], whereas the mortality rate was 0%. Two of the five cases were managed with an endovascular approach [19,43], while the rest with an open repair [35,39,41].…”
Section: Nm: Not Mentionedmentioning
confidence: 96%
See 3 more Smart Citations
“…Postoperative complications were reported in five cases (13.5%) [19,35,39,41,43], whereas the mortality rate was 0%. Two of the five cases were managed with an endovascular approach [19,43], while the rest with an open repair [35,39,41].…”
Section: Nm: Not Mentionedmentioning
confidence: 96%
“…Postoperative complications were reported in five cases (13.5%) [19,35,39,41,43], whereas the mortality rate was 0%. Two of the five cases were managed with an endovascular approach [19,43], while the rest with an open repair [35,39,41]. Ferrero et al reported that a 3.4 cm HAA previously treated with two multilayer stents showed a stent dislocation and sac expansion in 18 months follow-up [19].…”
Section: Nm: Not Mentionedmentioning
confidence: 96%
See 2 more Smart Citations